Las casas del deán don Juan de Córdoba: lujo y clientela en torno a un capitular del Renacimiento - Díaz Rodríguez, Antonio J. (2013)
Through different sources relating to don Juan Fernández de Córdoba, dean and canon of the cathedral of Cordova, abbot and lord of Rute, it tries to recreate an example of elite’s daily life and the mesh of links which formed the Cordovan society of the 16th century.